PENGENDALIAN INTERN DAN SIA UNTUK MENCEGAH FRAUD DALAM PERSEDIAAN BAHAN BAKU PADA PT X - Mussa, Nelcie Valensya; Agus Munandar (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Fraud is deviant behavior and consciously or intentionally that someone does for personal gain, to prevent fraud, internal control and fact structurers are needed. Both systems can assist management in monitoring PT X, in orther better about internal control system and SIA will minimize occurrence of fraud in the raw material inventory. The targets of this observe are (1) to apprehend and investigate at the impact of the internal control system on the prevention of fraud in the raw material inventory at PT X, (2) to understand and investigate the effect of the accounting information system on the prevention of fraud in the raw material inventory at PTX. The research method uses qualitative and quantitative methods. The sample used is the census sampling method in which the entire population is used as a sample, and the sample is 56 samples. This results obtained are (1) the inner manage device has an impact on fraud in raw material inventory (2) AIS has an effect on fraud in raw material inventory.